180 Days of Social Studies for First Grade : Practice, Assess, Diagnose. - Flynn, Kathy (180 Days of Practice Ser., 2018)
Build social studies content-area literacy with 180 days of daily practice! With these diagnostic-based activities, grade 1 students will analyze primary source documents, answer text-dependent questions, and build their social studies knowledge.